STUDENTS’ READING PROFICIENCY PROFILE AFTER ONLINE LEARNING IMPLEMENTATION ( A DESCRIPTIVE STUDY IN EIGHTH GRADERS OF MTS N 3 JEMBRANA) - Muhamad Nur Huda; I Nyoman Adi Jaya Putra; Dewa Ayu Eka Agustini (Universitas Pendidikan Ganesha, 2022)
The Covid 19 pandemic makes learning should be done via online (distance learning) which has different characteristics than before. The basic difference is on the existence of interaction during teaching and learning process. This research aims at investigating the students’ reading proficiency profile and classical learning mastery of eighth graders in MTS N 3 Jembrana after online learning is implemented. This research researh was categorized into descriptive quantitative. This research used survey sampling technique so 73 respondents were selected. The data of reading proficiency were collected by using test in the form of multiple choice. The collected data were analyzed descriptively by calculating the general and dimension mean of reading proficiency. This research discovers that 1) students’ reading competency is categorized into avarage, but specifically, finding main idea is categorized into average, finding textual reference is categorized into low, finding implixit information is categorized into low, finding explicit information is categorized very high, and finding sinonym and antonym is categorized in to very high and 2) the reading classical mastery is 41,01%. It implies that teaching reading online should be done based on communicative teaching reading principles